Cooperation metric for IEEE 802.11 wireless networks - Sadeghi, Rasool (2014)
A key design issue in relay based cooperative wireless networks is the design of an appropriate metric for relay selection algorithms. In most cooperative protocols designed for IEEE 802.11 networks, the relay selection metric is based on reducing the transmission delay of relay links. The bandwidth efficiency provided by this metric is beneficial for applications communicating at high data rate, however not all applications will benefit from this simple approach. In this paper, a novel cooperative metric is proposed, which in addition to bandwidth, also considers link reliability and link stability, especially useful in mobile scenarios, and for time sensitive service applications. The proposed metric is applied to the well-known CoopMAC protocol. Simulation results indicate a strong correlation between network performance and proposed cooperative metric.